Analisis Kemacetan Lalu Lintas di Kota Medan (Studi Kasus Jalan Gatot Subroto KP Lalang, Jalan Flamboyan Raya, Jalan KH. Syeikh Abdul Wahab Rokan Medan) - Can, Muhammad Qadriansyah; Batubara, Adellia Purnama (Universitas Batanghari Jambi, 2025)
This research aims to analyze traffic congestion in Medan City, especially on Jalan Gatot Subroto KP Lalang, Jalan Flamboyan Raya, Jalan KH. Sheikh Abdul Wahab Rokan Medan. The method used to analyze the performance of a road section is the 2014 Indonesian Road Capacity Guidelines. The results of calculations in this study conclude that the Gatot Subroto KP Lalang road has a class E service level, namely the traffic volume is approaching or at capacity, the flow is unstable, the speed sometimes stops , and it is recommended to provide traffic signs, increase parking spaces, carry out regular control of traders and socialize public transport drivers so that they do not stop anywhere on the road shoulder. The overall traffic flow shows significant changes with the degree of saturation (DS) on Jalan Syeikh Abdul Wahab Rokan still in the stable flow category, however on Jalan Gaharu the volume is above capacity and the queues are long (congested). The condition of the segments of Jalan Syeikh Abdul Wahab Rokan and Jalan Gaharu had a negative impact after a change in traffic direction with a significant increase in the degree of saturation (DS), dominated by vehicles entering and exiting Jalan Gaharu, many drivers going against the direction of the traffic flow, and there were vehicles who park in inappropriate places.